1.- Hallar E= (√3 + √2) ² - ( √3 - √2)² 2. si ab=4 ,a+b=3 Calcular a²+b² 3.- E =(x+1) (x-1) (x²+1) +1
Respuestas
Respuesta dada por:
0
Respuesta:
GG SO EZ
Trinomio cuadrado perfecto simplemente
Adjuntos:
![](https://es-static.z-dn.net/files/d7d/65e7eefc27387da98be0de84f5fff890.jpg)
![](https://es-static.z-dn.net/files/d72/3837acadaaa8f24d47b8a70288b74d40.jpg)
![](https://es-static.z-dn.net/files/dd9/9d9d1c3a346cc927e4e76ece8bbd07da.jpg)
Preguntas similares
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años